T cell receptor diversity, specificity and promiscuity of functionally heterogeneous human MR1-restricted T cells. (February 2021) - Lepore, Marco; Lewinsohn, Deborah A.; Lewinsohn, David M.
Highlights: MR1 can present multiple distinct ligands to T cells. Diverse Human MR1 restricted T cells recognise distinct microbial or self/tumour antigens. Individual MR1-restricted TCR display ligand discriminations. Some MR1-restricted TCRs are cross-reactive toward multiple ligands. Human MR1-restricted T cells are functionally heterogeneous. Abstract: The monomorphic MHC-class I-like molecule, MR1, presents small metabolites to T cells. MR1 is the restriction element for microbe-reactive mucosal-associated invariant T (MAIT) cells. MAIT cells have limited TCR usage, including a semi-invariant TCR alpha chain and express high levels of CD161 and CD26. In addition to microbial lumazine metabolites, recent studies have demonstrated that MR1 is able to capture a variety of diverse chemical entities including folate-derivatives, a number of drug-like and other synthetic small molecules, and as yet undefined compounds of self-origin. This capacity of MR1 to bind distinct ligands likely accounts for the recent identification of additional, non-canonical, subsets of MR1-restricted T (MR1T) cells. These subsets can be defined based on their ability to recognize diverse microbes as well as their reactivity to non-microbial cell-endogenous ligands, including tumor-associated antigens. Herein, we will discuss our current understanding of MR1T cell diversity in terms of TCR usage, ligand recognition and functional attributes.